Variable mafic recharge across a caldera cycle at Rabaul, Papua New Guinea - Fabbro, Gareth N. (2020)
The size of eruptions from calderas varies greatly, from small effusive eruptions that pose danger only in the immediate vicinity of the vent, to large, caldera-forming events with global impact. However, we currently have little way of knowing the size of the next eruption. Here, we focus on Rabaul Caldera, Papua New Guinea, to investigate differences between the magmatic processes that occurred prior to the >11-km3 caldera-forming “1400 BP” Rabaul Pyroclastics eruption and prior to subsequent, smaller (<1 km3) post-caldera eruptions. During the current, post-caldera phase, basaltic enclaves and mafic minerals are common among the erupted products, indicating basalt has been free to enter the mobile, dacite-dominated region of the sub-caldera plumbing system. Many of the post-caldera magmas are hybrid andesites, reflecting the importance of mixing and mingling of basaltic and dacitic magmas during this period. In contrast, before the Rabaul Pyroclastics eruption, the recharge was an andesite that was not the product of mixing basalt and dacite. The lack of basaltic recharge prior to the Rabaul Pyroclastics eruption suggests basalt was prevented from entering the shallow, sub-caldera magma system at that time, possibly by the presence of a large, silicic, melt-dominated body. That basalt can currently enter the shallow system is consistent with reduced thermal and rheological contrasts between the recharge and resident magma, implying a similar large silicic melt body currently does not exist beneath the caldera. If this hypothesis is correct, it may be possible to track the growth and evolution of large magma reservoirs that feed caldera-forming eruptions by monitoring the petrology of eruptive products.